Comparison Between Metabolic Syndrome and the Framingham Risk Score as Predictors of Cardiovascular Diseases Among Kazakhs in Xinjiang. Issue 1 (December 2018) - Yang, Wenwen; Ma, Rulin; Zhang, Xianghui; Guo, Heng; He, Jia; Mao, Lei; Mu, Lati; Hu, Yunhua; Yan, Yizhong; Liu, Jiaming; Ma, Jiaolong; Li, Shugang; et al.
Abstract Metabolic syndrome (MS) and Framingham risk score (FRS) can be used for predicting the risk of developing cardiovascular diseases (CVD). Previous studies that compared FRS and MS have focused on high-income urban areas. This study focused on the comparison between FRS and MS when used in nomadic minorities in mountain areas. Moreover, an applicable tool for predicting the risk of developing CVD was identified. 2, 286 participants who were recruited from the far west of China were followed-up for a median of 5.49 years. MS and FRS were compared in terms of their ability in predicting development of CVD using Cox regression and receiver operating characteristic curve. After each component of MS was appraised, its area under the curve (AUC) was 0.647. When age was included, the AUC of MS risk score increased from 0.647 to 0.758 (P < 0.001). After adjusting for age, the AUC of FRS decreased from 0.732 to 0.582 (P < 0.001). The association between CVD and each quintile of MS risk score that included age was more significant than that between FRS and CVD under the same exposed condition. In conclusion, MS risk score that included age may be a better predictor of CVD among Kazakhs.